A review of congenital tremor type A-II in piglets. (18th June 2020) - Stenberg, Hedvig; Jacobson, Magdalena; Malmberg, Maja
Abstract: Congenital tremor (CT) is a neurological disease that affects new-born piglets. It was described in 1922 and six different forms, designated type AI-V and type B, are described based on the causative agents, as well as specific histological findings in the central nervous system (CNS). The various forms present with identical clinical signs consisting of mild to severe tremor of the head and body, sometimes complicated with ataxia. By definition, all A-forms have hypomyelination of the CNS, whereas there are no histopathological lesions with the B-form. The cause of the A-II form was long unknown, however, at present several different viruses have been proposed as the causative agent: porcine circovirus-II (PCV-II), astrovirus, PCV-like virus P1, and atypical porcine pestivirus (APPV). Currently, APPV is the only virus that has been proven to fulfill Mokili's Metagenomic Koch's Postulates. Following infection of the pregnant sow, the virus passes the placental barrier and infects the fetus. Interestingly, no clinical signs of disease have been associated with APPV in adult pigs. Furthermore, other viruses cannot be ruled out as additional potential causes of CT. Given the increased interest and research in CT type A-II, the aim of this review is to summarize current knowledge.